Prevalence of chronic ankle instability among senior high school basketball athletes: a cross-sectional study - Erit Rovendra; Novi Wulan Sari (Poltekkes Kemenkes Bandung, 2026)
Background: Ankle injuries are among the most common injuries in basketball athletes, with lateral ligament sprains being the most frequently diagnosed condition. These injuries may lead to chronic ankle instability (CAI), a condition characterized by recurrent ankle sprains accompanied by a sensation of giving way or instability during physical activity. Objective: This study aimed to identify the prevalence of chronic ankle instability among high school basketball athletes in Bukittinggi City. Methods: This study used an analytical cross-sectional design and was conducted from March to May 2024. The study population consisted of high school basketball athletes in Bukittinggi City. Participants were selected using a purposive sampling technique, with a total sample of 162 athletes. Data were collected once from each respondent using the Cumberland Ankle Instability Tool (CAIT), in which a score of less than 24 was categorized as CAI. Additional variables included gender, body mass index (BMI), history of ankle sprain, and medical treatment after injury. Data were analyzed descriptively and using chi-square tests to examine associations between variables. Results: The prevalence of CAI was 51.2%. A higher proportion of CAI was observed among male athletes, those with overweight BMI, those with a history of ankle sprain, and those who received medical treatment after injury. Conclusion: CAI prevalence among high school basketball athletes in Bukittinggi is high, indicating the need for early screening and proper injury management strategies.